2023
DOI: 10.3389/fphys.2023.1127474
|View full text |Cite
|
Sign up to set email alerts
|

Delayed denervation-induced muscle atrophy in Opg knockout mice

Abstract: Recent evidence has shown a crucial role for the osteoprotegerin/receptor activator of nuclear factor κ-B ligand/RANK (OPG/RANKL/RANK) signaling axis not only in bone but also in muscle tissue; however, there is still a lack of understanding of its effects on muscle atrophy. Here, we found that denervated Opg knockout mice displayed better functional recovery and delayed muscle atrophy, especially in a specific type IIB fiber. Moreover, OPG deficiency promoted milder activation of the ubiquitin-proteasome path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…revealed that Tet2 deficiency compromises the regenerative ability and myotube fusion in skeletal muscle [ 64 ]. Strategies aimed at enhancing Tet2 stability or ensuring its elevated expression have been shown to reduce the effects of denervation-induced muscle atrophy and improve skeletal muscle function in the context of obesity [ 65 , 66 ]. Further investigation has shown that Tet2 deficiency disrupts the proliferation and differentiation of SCs, a process mediated by the calcium signaling gene Slc8a3 and Myog , a critical regulator of myogenesis [ 63 , 64 ].…”
Section: The Role Of Epigenetic In Skeletal Muscle Atrophymentioning
confidence: 99%
“…revealed that Tet2 deficiency compromises the regenerative ability and myotube fusion in skeletal muscle [ 64 ]. Strategies aimed at enhancing Tet2 stability or ensuring its elevated expression have been shown to reduce the effects of denervation-induced muscle atrophy and improve skeletal muscle function in the context of obesity [ 65 , 66 ]. Further investigation has shown that Tet2 deficiency disrupts the proliferation and differentiation of SCs, a process mediated by the calcium signaling gene Slc8a3 and Myog , a critical regulator of myogenesis [ 63 , 64 ].…”
Section: The Role Of Epigenetic In Skeletal Muscle Atrophymentioning
confidence: 99%